Sources of individual variability in a pragmatic reference game: Effects of logical reasoning and Theory of Mind - Alexandra Mayn; Vera Demberg (PLoS ONE, 2026)
While in theory people are expected to adhere to rational communicative principles, a growing body of work shows that people vary widely in their tendency to draw pragmatic inferences. It has been suggested that these differences may, in part, stem from depth of reasoning: Previous work has shown that individual participants’ response patterns in a pragmatic reference game are predicted by three probabilistic pragmatic models of different reasoning depth. However, those models are agnostic to the cognitive traits which underlie those differences. In this study, we systematically investigate sources of individual variation in a pragmatic reference game, where participants are required to draw ad-hoc implicatures of various complexity. We relate the observed variability in reference game performance to cognitive traits, specifically logical reasoning ability, working memory and Theory of Mind, as well as to the strategies reported by participants. We find a positive effect of logical reasoning and Theory of Mind on pragmatic inference. We do not find evidence for an effect of working memory.